Inhibitory Effect of Kaffir Lime, Bitter Cucumber and Tobacco Extracts on The Growth of Aspergillus flavus - Thanaboripat*, Dusanee; Chareonsettasilp, Sittichai; Pandee, Kanokwan; Udomwongsup, Kittipun (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Crude ethanolic extracts of kaffir lime leaf, bitter cucumber fruit and tobacco leaf were examined for their ability to control the growth of A. flavus on PDA. The results showed that the ethanolic extracts of all herbs had an inhibitory effect on fungal growth. Kaffir lime at 10 % and tobacco at 8-10% showed significantly higher inhibition than at other concentrations whereas bitter cucumber at 6, 8 and 10% gave a similar inhibitory effect on the fungus. Keywords: herb, medicinal plant, aflatoxin producing fungi, Aspergillus flavus Corresponding author: E-mail: ktdusane@kmitl.ac.th